Design, Synthesis and Antibacterial Activity of Certain Novel Indole-glyoxylamide Conjugates - Chellamuthu, Buvana; Ramalingam, Suresh; Haribabu, Yellina (Indian Journal of Pharmaceutical Education and Research, 2022)
Objectives: To synthesize 2-Aryl 3-substituted indole-glyoxylamides to evaluate their antibacterial activity on target protein (4DH6). Materials and Methods: Computational techniques: The fused heterocyclic compound indole linked with glyoxylamide was designed by using computational techniques and also energy minimized. The molecular property and biological activities is determined by mol inspiration tool. The antibacterial target receptor/protein (PDB ID: 4DH6) have been selected for the docking studies. Experimental work: Synthesis of 2-aryl indol-3-yl glyoxylamide derivatives by reaction of 2-phenylindole condensed with oxalyl chloride and different amines in one pot reaction. Spectral characterization and antibacterial activity: The synthesized lead molecules were characterized by means of FTIR, ESI-Mass spectral analysis and tested for their antibacterial activity by using agar well plate diffusion method. Results: The lead molecules were selected based on high binding affinity on target receptor 4DH6. The selected lead molecule was synthesized and the functional group, molecular weight, number of proton is identified by FTIR, ESI-Mass and 1HNMR respectively. The purity of the compound was determined by melting point and TLC. Antibacterial activities of synthesized lead compounds were active against gram positive bacteria Bacillus subtilis and gram-negative bacteria Escherichia coli at a concentration of 100μg/ml. Conclusion: In the present work indicates that nitro (NO2) and chloro (Cl) substituted 2 –Aryl indole 3- Glyoxylamide derivatives showed potent antibacterial activity against both gram positive Bacillus subtilis and gram negative E.coli. Hence this study will used to design of more potent antibacterial agents for therapeutic use.
Keywords: Auto dock; Molinspiration FTIR; ESI-MASS; Antimicrobial activity